The mediation effects of consumers' need recognition and pre-purchase evaluation in consumers' decision-making on purchasing safe street food: The case in Nakhon Si Thammarat, Thailand. Issue 2 (15th March 2017) - Khongtong, Jatuporn; Karim, Muhammad Shahrim; Othman, Mohhidin; Bolong, Jusang Bin
ABSTRACT: Nakhon Si Thammarat province is one of the largest cities in Thailand and offers various types of street foods in the city. However, the number of street vendors that pass food safety certification is very low. Nevertheless, there are many consumers who still purchase street food because of their lifestyle who are exposed to food safety risks. Therefore, this research aims to evaluate how consumers make their decisions about the safety of the street food. This study investigates the importance of the need recognition and pre-purchase evaluation stages in consumers' decision-making in relation to their purchasing of safe street food. The results from the structural equation modeling analysis found that, at 95%, the confidential need recognition would act as a partial mediator between consumers' motivation → pre-purchase evaluation on purchasing safe food and consumers' food safety knowledge → pre-purchase evaluation. In turn, pre-purchase evaluation would act as a full mediator between consumers' motivation and safe street food purchasing. The findings signify that the stages of need recognition and pre-purchase evaluation in the decision-making process are important in order to reduce consumers' food risk while purchasing street food. Therefore, encouraging consumers to recognize the importance of purchasing safe food and convincing them to be concerned when selecting food is necessary to prevent consumers from unsafe food consumption.